Determinasi Budaya Organisasi dan Disiplin Kerja terhadap Kinerja Guru SMA Swasta Buddhis di Banten - Mega Puri Ratna (Institut Nalanda, 2025)
Educational institutions are basic, planned efforts to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, morals, life sciences, general knowledge and the skills they need for society based on law. -Laws are complex institutions. Teachers are professional educators who educate, teach knowledge, guide, train, assess and evaluate students. Therefore, to produce quality students, teachers must have good performance. Factors that can have an impact on teacher performance include: how to practice organizational culture, teacher discipline when carrying out teaching, and the results achieved by teachers in carrying out teaching. Based on the survey, it is known that the performance of private Buddhist high school (SMA) teachers in Banten province is still not optimal, so there is a need for improvement.